The Cultural Intermediaries Reader (Jennifer Smith Maguire and Julian Matthews, eds.: Sage, 2014) - Humphries, Jane (Irish Journal of Arts Management and Cultural Policy, 2017)
A review of the conceptualisations of ‘cultural intermediaries’ in The Cultural Intermediaries Reader, edited by Jennifer Smith Maguire and Julian Mathews. In The Cultural Intermediaries Reader, Jennifer Smith Maguire and Julian Mathews aim to offer the first comprehensive introduction to the contemporary conceptualisation of cultural intermediaries. In the introduction, the editors offer an initial definition of cultural intermediaries as the taste makers defining what counts as good taste and cool culture in today’s marketplace. Working at the intersection of culture and economy, they perform critical operations in the production and promotion of consumption, constructing legitimacy and adding value through the qualification of goods. (p.1)